ANALISIS KEMAMPUAN SISWA SEKOLAH DASAR DALAM MENGEMBANGKAN SIKAP TOLERANSI DAN EMPATI MELALUI PEMBELAJARAN IPS - Sari, Yunistira; Nuraeni, Erin; Nadia, Shiva; Miladiyah, Miladiyah; Marisa, Puput; Ratnasari, Dine Trio (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
This study aims to analyze in-depth the ability of elementary school students to develop attitudes of tolerance and empathy through Social Studies (IPS) learning. This study is motivated by the phenomenon of social studies education, which is often dominated by strengthening cognitive aspects, resulting in insufficient attention to the development of the affective domain, particularly the values ??of tolerance and empathy, which are crucial for national diversity. Using a qualitative approach with descriptive methods, the study involved fifth-grade students SDN 4 Muara Ciujung  and teachers selected through purposive sampling. Data were collected through observation, interviews, and documentation. The research findings revealed that the implementation of student-centered learning models, such as cooperative learning, role-playing, and project-based learning, effectively stimulated positive social interactions and fostered mutual respect. Teachers play a vital role as facilitators and role models, although the internalization of these values ??is not yet fully widespread due to the influence of the family environment and an evaluation orientation that is still focused on academic achievement. The main conclusion confirms that social studies learning plays a strategic role in shaping students' tolerant and empathetic character from an early age, which requires a paradigm shift from merely transferring knowledge to strengthening social character to maintain harmony in diversity. ABSTRAK Penelitian ini bertujuan untuk menganalisis secara mendalam kemampuan siswa sekolah dasar dalam mengembangkan sikap toleransi dan empati melalui pembelajaran Ilmu Pengetahuan Sosial (IPS). Studi ini dilatarbelakangi oleh fenomena pendidikan IPS yang seringkali didominasi oleh penguatan aspek kognitif, sehingga pengembangan ranah afektif, khususnya nilai toleransi dan empati yang krusial bagi kemajemukan bangsa, kurang mendapatkan perhatian yang memadai. Menggunakan pendekatan kualitatif dengan metode deskriptif, penelitian melibatkan siswa kelas V SDN 4 Muara Ciujung  dan guru yang dipilih melalui teknik purposive sampling, dengan pengumpulan data melalui observasi, wawancara, dan dokumentasi. Temuan penelitian mengungkapkan bahwa implementasi model pembelajaran yang berpusat pada siswa, seperti cooperative learning, role playing, dan project-based learning, efektif menstimulasi interaksi sosial positif dan menumbuhkan sikap saling menghargai. Guru memegang peran vital sebagai fasilitator dan model keteladanan, meskipun internalisasi nilai tersebut belum sepenuhnya merata akibat pengaruh lingkungan keluarga dan orientasi evaluasi yang masih terpaku pada capaian akademik. Simpulan utama menegaskan bahwa pembelajaran IPS memiliki posisi strategis dalam membentuk karakter toleran dan empatik siswa sejak dini, yang menuntut adanya pergeseran paradigma dari sekadar transfer pengetahuan menuju penguatan karakter sosial demi menjaga harmoni kebinekaan.